The Effect of Strategy-Based Instruction on EFL University Students’ Writing Performance: A Study at the University of Benghazi, Al-Abyar Branch (Comprehensive Journal of Science, 2025)
Developing writing proficiency in English as a Foreign Language (EFL) remains a significant challenge, particularly at the university level. Conventional teaching approaches, which emphasize grammatical correctness and imitation of model texts, often constrain students’ ability to generate ideas and organize coherent essays. This study investigated the relative effectiveness of a strategy-based instructional approach in comparison to traditional methods at the University of Benghazi, Al-Abyar branch. A quasi-experimental design was employed with an experimental group and a control group. Writing performance was measured through pre- and post-tests, and the data were analyzed using descriptive statistics, paired-samples *t* tests, one-way Analysis of Variance (ANOVA), and Mixed ANOVA. The findings indicate that the experimental group exhibited significantly greater improvement in writing performance than the control group. These results underscore the value of integrating strategy-based instruction into EFL writing curricula in higher education contexts.
Keywords: writing instruction, strategy-based approach, traditional methods, EFL learners, academic writing